Ba6Zn7Ga2S16: A Wide Band Gap Sulfide with Phase-Matchable Infrared NLO Properties - Li, Yan-Yan; Liu, Peng-Fei; Wu, Li-Ming (Chemistry of materials, 2017)
High-performance infrared (IR) nonlinear optical (NLO) materials with large laser damage thresholds (LDTs) are urgently needed because the current commercially available AgGaS2, AgGaSe2, and ZnGeP2 suffer their very low LDTs which shorten significantly their service lifetimes. Here, a novel sulfide, Ba6Zn7Ga2S16 with a very wide band gap of 3.5 eV, has been discovered. This compound crystallizes in the chiral trigonal R3 space group with a novel 3D framework that is constructed by ZnS4 tetrahedra, Zn3GaS10 supertetrahedra (a T2-type), and Zn3GaS10 quadri-tetrahedral clusters via vertex-sharing. Such a novel structure exhibits desirable features which suggest a promising NLO material: phase-matchability (PM), good NLO efficiency (about half that of benchmark AgGaS2), and the highest LDT among PM chalcogenides (28 times that of benchmark AgGaS2). In addition, the density functional theory (DFT) calculations confirm its PM behavior and reveal that the second harmonic generation (SHG) origin is mainly ascribed to the transition process from S-3p to Ga-4p, Zn-3p, Zn-3d, and Ba-5d states; the calculated d 11 coefficient of 6.1 pm/V agrees well with experimental values.